The Selection - Cass, Kiera (New York : HarperTeen, 2012)
America Singer is chosen to compete in the Selection--a contest to see which girl can win the heart of Illea's prince--but all she really wants is a chance for a future with her secret love, Aspen, who is a caste below her.
Keywords: Contests -- Juvenile fiction; Social classes -- Juvenile fiction; Princes -- Juvenile fiction; Marriage -- Juvenile fiction; Revolutionaries -- Juvenile fiction; Dystopias -- Juvenile fiction; Love stories